De-novo use of generic tacrolimus (Adoport) in renal transplant recipients: A single center experience from Türkiye - Koç, Neriman Sıla; Yıldırım, Tolga; Yılmaz, Şeref Rahmi; Erdem, Yunus (Acta Medica, 2024)
Objective: Renal transplantation is the best treatment for end-stage kidney disease, and tacrolimus has become an important immunosuppressive treatment for kidney transplant patients since it was introduced. After the first generic tacrolimus has been approved by the FDA, studies have begun to compare the effectiveness and safety of generic tacrolimus with the original tacrolimus. When using generic immunosuppressive therapies, it is also necessary to ensure that it provides adequate immunosuppression and does not cause severe toxicity. This study aims to compare clinical outcomes, including acute rejection, graft loss and adverse reactions, in patients receiving brand tacrolimus (Prograf, Astellas Pharma, U.S.) or generic tacrolimus (Adoport, Sandoz, UK) from the start of kidney transplant therapy. Study Design: Renal transplant recipients between 1 January 2015-1 March 2020 were screened retrospectively. All patients receiving de novo generic tacrolimus (n:51) and randomly selected 102 control renal transplant recipients receiving original tacrolimus were included in this study. Materials and Methods: We evaluated and recorded demographic, clinical and laboratory data including age, gender, primary kidney disease, donor type (live or dead), induction and death regimen, tacrolimus dose, tacrolimus through levels, serum creatinine, biopsy-confirmed acute rejection episodes, delayed transplant function, positive BK polyomavirus in the urine, BK polyomavirus-related nephropathy, cytomegalovirus infection in 1-year follow-up. Results: Most of the patients were male (64.1%) with a mean age of 38.3 years. There was no significant difference in demographic characteristics between the original and generic tacrolimus groups. No differences were found in terms of creatinine levels, total daily dose of tacrolimus and tacrolimus trough levels at discharge and the first year. Additionally, biopsy-confirmed acute rejection in the following year after transplantation, BKPyV positivity in urine, BKPyVAN, CMV viremia and adverse reactions related to tacrolimus were similar between the two groups. Conclusion: With this study, we aimed to contribute to the literature with our experience on the use of generic tacrolimus from our country. As a result of our study, we noted that generic tacrolimus can be safely preferred for de-novo use with close drug-level monitoring because it is an immunosuppressant agent with a narrow therapeutic index. There is a continuing need for randomized prospective-designed and multi-centric studies with a wide range of patients.